Genetic variation among populations of, and evidence of deep divergence within, the Rio Grande Chirping Frog, Eleutherodactylus campi (Anura: Eleutherodactylidae) - Beshera, Kebede A.; Williams, Avery A.; Hamlin, John A.; Bergeaux, Peter J.; Morgan, Christian C.; Armstrong, Aubrey N. (Zootaxa, 2022)
Herein we report the first molecular assessment of intra-species genetic variation and interrelationships within the Rio Grande Chirping frog, Eleutherodactylus campi. We analyzed 548 base pairs of 16S rRNA gene for 71 ingroup individuals belonging to the genus Eleutherodactylus (including 42 E. campi sampled from 15 localities in the United States and Mexico) and four outgroup samples. By unveiling two highly divergent and geographically structured clades within E. campi this study provides a novel phylogenetic placement of E. campi populations north and south of the Rio Grande Valley as sister groups to each other. The observed level of genetic divergence between these two clades (5.8%) is, on average, comparable to or greater than the levels of divergence found between several currently valid amphibian species pairs. Estimates of Time to Most Common Ancestor (TMRCA) indicate that the phylogeographic split between the two E. campi clades may have occurred 7.6 MYA (i.e., late Miocene), consistent with the geologic history of southwestern North America. The study also confirms that south Texas served as the source population for populations of E. campi in its introduced range (i.e., Alabama, Louisiana, and Texas). Overall, this molecular study indicates that E. campi consists of two deeply divergent lineages corresponding to its populations north and south of Rio Grande Valley. These results suggest that the recovered lineages may represent independent species and thereby highlight the need for further research to clarify their status.